Assessing the impact of tax/transfer policy changes on poverty: Methodological issues and some European evidence - Tim Callan; John Walsh (University of Essex, Institute for Social and Economic Research (ISER), 2006)
A method of systematically assessing the “first-round” impact of tax and transfer policy changes on the income distribution and the incidence of relative income poverty is proposed. It involves the construction of a “distributionally neutral” policy, which can be approximated by a policy which indexes tax allowances, credits and bands and welfare payment rates in line with a broad measure of income growth. The impact of actual policy changes in five EU countries over the 1998 to 2001 period is then measured against this benchmark, using the EUROMOD tax-benefit model.
Keywords: H23; H53; I32; 330; Distributive impact; relative income poverty; microsimulation